SAT-205 ESR1 Q375H and R394H Mutants Associated with Estrogen Insensitivity Syndrome Mediate Genome-Wide Genetic and Epigenetic Aberrances - Li, Yin (J Endocr Soc, 2019)
Estrogen insensitivity syndrome (EIS) or estrogen resistance is very rare and most commonly caused by a mutation in ERα that results in the inability of estrogen to exert its biological effects. However, mutations in ESR1 gene and the underlying molecular mechanisms have not been thoroughly studied. We investigated the structural conformation, whole transcriptome, and DNA methylome for the ERα natural mutants, ESR1 Q375H and R394H that associated with EIS patients. We indicate that Q375H located in the coactivator binding pocket, while R394H located in the ligand binding pocket of the ERα ligand binding domain. Both mutants have changed the ERα structure conformation. We also demonstrate that both mutants differentially mediated whole transcriptome and DNA methylome aberrations in the genome. These mutants result in losing alteration to the estrogen-response genes predominantly when compared to WT ERα. To investigate the biological characterization of this natural mutation in vivo, a mouse model was generated harboring the human mutation, Esr1-Q379H (Esr1-Q), using CRISPR-/Cas9 and both male and female mice were analyzed. Our preliminary examinations show that the female and male Esr1-Q and αERKO mice were consistently more obese than the wild type (WT) mice. Female Esr1-Q mice have hemorrhagic cystic ovaries, rudimentary mammary ducts and hypoplastic uteri. In addition, the Esr1-Q mice have elevated levels of luteinizing hormone (LH) and nearly all examined phenotypes mirror those observed in αERKO mice. To test the responsiveness to estrogen in the Esr1-Q mice, a three-day bioassay with diethylstilbestrol (DES, a synthetic estrogen) was performed. WT uterine weight increased in the DES group when compared to controls. However, Esr1-Q uterine weight did not change with DES treatment, suggesting that this natural mutant lost ERα function. The female patient was also non-responsive to a high-dose estrogen treatment. The Esr1-Q male mice are infertile and show increased seminal vesicle weights as well as seminiferous tubule disruption in the testes. These findings provide an important basis for understanding the molecular and cellular mechanism of EIS and the mouse model offers a potential new way to study rare genetic receptor mutations in humans with hopes of developing a viable therapeutic approach.